(untitled) (CIPEEX, 2025)
Introduction: Pulsed electromagnetic field (PEMF) stimulation has gained attention in health and performance sciences, being used to assist muscle recovery. Objectives: To evaluate the efficacy of PEMF in accelerating lactate removal in participants after an exhaustive sprint running protocol. Methods: Four participants of both sexes completed two visits. Lactate measurements were taken at baseline, immediately after exercise, and at 5, 10, 15, and 30 minutes post-exercise. The protocol consisted of ten 75-meter sprints with 30-second intervals. In one condition, PEMF was applied to accelerate muscle recovery; in the other, recovery was passive (rest). Results: Lactate peaked 5 minutes post-exercise. Both conditions showed a reduction in lactate concentrations, but the control group had higher mean values (83%) compared to the PEMF group (76%). Paired t-tests showed no statistical significance at immediate (p=0.0592), 15 minutes (p=0.0833), and 30 minutes (p=0.0784) post-exercise. Conclusion: PEMF did not demonstrate improved lactate removal at the evaluated time points; however, the results suggest that a larger sample size may achieve statistical significance.